Case Report: Retropancreatic fascia hernia protruding into the thoracic cavity through a Bochdalek hernia - Nakagawa, Yoichi; Maeda, Takuya; Uchida, Hiroo; Takada, Shunya; Hinoki, Akinari; Shirota, Chiyoe; Tainaka, Takahisa; Sumida, Wataru; Makita, Satoshi; Amano, Hizuru; Takimoto, Aitaro; Gohda, Yousuke (Frontiers in Pediatrics, 2023)
Retropancreatic fascia hernia is a novel internal hernia originating from the retropancreatic fascial defect, which subsequently expands towards the dorsal aspect of the pancreatic body and migrates into the retroperitoneal space. We encountered a rare case of concomitant retropancreatic fascia and Bochdalek hernias. Here, we describe the imaging characteristics of this hernia type and its surgical strategies.